2009
DOI: 10.1117/12.826625
|View full text |Cite
|
Sign up to set email alerts
|

Progress toward a complete metrology set for the International X-ray Observatory (IXO) soft x-ray mirrors

Abstract: We present an overview update of the metrologic approach to be employed for the segmented mirror fabrication for the IXO soft x-ray telescope. We compare results achieved to date with mission requirements. This is discussed in terms of inherent capability versus in-practice capability of the metrology. We find that all the needed metrology equipment are in hand but that a number of the needed quantities remain too uncertain relative to mission requirements. This is driven by the mounting of the mirrors themsel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…After oxidation, in step 2, the mirror front side is measured by a metrology tool at GSFC, which is an interferometer with a cylindrical null. 16 We have found that the measured surface figure before and after oxidation is unchanged (within 10 nm in RMS height), indicating the integrated stress field in the back side oxide is the same as that on the front side. The surface topology map M 1 measured in step 2 is used as the mirror's initial figure.…”
Section: Processmentioning
confidence: 81%
“…After oxidation, in step 2, the mirror front side is measured by a metrology tool at GSFC, which is an interferometer with a cylindrical null. 16 We have found that the measured surface figure before and after oxidation is unchanged (within 10 nm in RMS height), indicating the integrated stress field in the back side oxide is the same as that on the front side. The surface topology map M 1 measured in step 2 is used as the mirror's initial figure.…”
Section: Processmentioning
confidence: 81%
“…Typically, the fabricated mirror segments are 30-degrees wide in the circumferential direction. The mirrors are measured in 3-point, 4-point, or 8-point Cantor Tree mount [2][3][4] .…”
Section: Optical Performance Modelingmentioning
confidence: 99%
“…The IXO project at Goddard Space Flight Center has developed metrology techniques suitable [2][3][4] for the mirror surface metrology of grazing incidence mirrors. For the segmented mirrors of full revolution normal incidence metrology can be used.…”
Section: Introductionmentioning
confidence: 99%
“…It copies the figure of conventionally fabricated mandrels to cOlllIJlercially procured (Schott D263) thin (-0.4 mm) float glass sheets while preserving their excellent micro-roughness (-4A rms measured over a 300 /lm span). As shown in Figure 2 (right panel), it has been able to make mirror substrates consistently at -6.5 are-seconds (HPD); Each entry in the histogram represents a substrate pair which has been precisely measured with optical metrology [19,20,21,22,23,24] and whose x-ray imaging performance calculated with standard performance prediction techniques. The glass slumping process is capable of making substrates the meet the requirements of a sub-l0 arc-second mirror assembly: It has been used to making the more than 10,000 substrates for the NuST AR mission [7].…”
Section: Technical Approaches and Statusmentioning
confidence: 99%